Analysis of Educational Factors in the Development of Human Resource Capacity at the Library and Archives Office of Ciamis Regency - Ati Lathifah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This research is motivated by the suboptimal development of human resource capacity in the Ciamis County Library and Archives Office due to the mismatch in employees' educational backgrounds. The aim of this study is to determine how the development of human resource capacity is conducted in the Ciamis County Library and Archives Office. The method used in this study is qualitative with a descriptive approach. The number of informants is 5 people, and the data collection techniques used in this study include observation, interviews, and documentation. The data processing/analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results of the study show that the development of human resource capacity in the Ciamis County Library and Archives Office has not been carried out optimally. The challenges faced by the Ciamis Regency Library and Archive Office include the placement of work according to the educational background of employees, where the limited number of employees with educational backgrounds suitable for certain positions is a key issue. This results in some positions being filled by employees with less relevant educational backgrounds to keep the organization running smoothly. Efforts to address this problem include providing training and technical guidance by the agency to ensure employees can perform their tasks well. This placement approach, which considers various factors, demonstrates a commitment to optimizing the development of human resource capacity at the Ciamis Regency Library and Archive Office.